KOMUNIKASI PROMOSI TANGKELEK PADA TEMA PRODUKDALAM MEMBANGUN PESAN TERHADAP KONSUMEN - WAHYUNI PERMATA SARI; Dora Tiara; Kiki Yulinda (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
Seeing the success that PT. Dagadu Aseli and Joger as iconic brands that are characteristic of Yogya and Bali, Kadai Tangkelek has also tried to follow the same path. The main target market for Kadai Tangkelek is tourists who make these products as souvenirs to be brought to their home areas. Especially after the earthquake in 2009, the city of Padang was crowded with volunteers from various parts of Indonesia, including neighboring countries who also sent aid. The business concept promoted by Tangkelek is creativity that elevates Minangkabau culture as a culture rich in positive values ??of life. The term Minangkabau itself describes a culture. Minangkabau culture, especially the language is used in most parts of West Sumatra and is used in several other areas where Minangkabau migrants are located. Minangkabau is spoken in West Sumatra Province, in several areas on the border of Jambi Province (along the Batanghari River), in Kampar District, Riau Province, and is used by Jamee groups (West Aceh), and in Negeri Sembilan (Malaysia). So that the Minangkabau culture and language itself has been known and spread in various regions.